PBL dalam Blended Learning untuk Meningkatkan Kemampuan Berpikir Kritis dan Pemecahan Masalah - Wening Kusumawardani; Tien Aminatun (Jurnal Penelitian Pendidikan IPA, 2024)
This study explores how PBL integrated into blended learning affects the enhancement of critical thinking and problem-solving skills among senior high school students. It employs a quasi-experimental design involving a non-equivalent pretest-posttest control group. Participants consist of students from class X-5 assigned to the experimental group and students from class X-8 assigned to the control group. Data were collected using a validated description test to measure critical thinking and problem-solving skills. Analysis involved MANOVA, N-Gain calculation, and the Pearson correlation test. Findings indicate that implementing PBL in blended learning effectively improves critical thinking and problem-solving abilities. The experimental group's average post-test score for critical thinking was 85.83, compared to 75.42 in the control group, and for problem-solving, it was 85.56, compared to 71.67 in the control group.